PERANAN FATIGUE CHECK TERHADAP KEBUGARAN KERJA DI PT.PAMA PERSADA NUSANTARA DISTRICT KPCS SANGATTA - Setyanto, Puguh (PREDIKSI, 2016)
The purpose of this study was to know the role of the Centre Against Fatigue Check Work PT. Pama Persada Nusantara Sangatta District KPCS. The timing of the research conducted in January 2016 through May 2016 for five (5) months.The research method in this study is a qualitative descriptive research on how the role of fatigue fitness check to work in PT. Pama Persada Nusantara Sangatta District KPCS. The collection of data by distributing questionnaires, observation and interviews.The study states that the role of fatigue fitness check to work in PT. Pama Persada Nusantara District KPCS Sengata goes well, fatique check the physical and mental conditions of employees of PT. Pama Persada Nusantara on job sites has always maintained his fitness and is always ready to work.